The Resources Management Movement (The Coming Death of Production Management Education) - Schonberger, Richard J. (Academy of Management Journal, 1972)
The article discusses the problems associate with students' attitudes toward production management courses in business education. According to the author, students view these courses in negative light, often confusing them with manufacturing courses, when many of them do not to be involved in manufacturing industries. He suggests several ways that educators can encourage more students to take these courses since they are important to the future generations of managers. One of the ways that is suggested is having textbooks de-emphasize the role of manufacturing in production management. He then calls for the name of the courses to be called ?resource management,? since production has more to do with managing resources.